Swearing Words in Holy Scriptures: A Pragmatic Study of the Quran - Reranta, Redika Cindra; Setiawan, Rifki Hanif; Putri, Elsa Hana Rahma; Safira, Tiara Putri (TEKNOSASTIK, 2024)
The term "swearing words" refers to diction that is deemed taboo, unpleasant, cursing, and restricted in discourse. However, there is no way to avoid it. It has so existed since the beginning of human spoken communication and continues to this day. The purpose of this paper is to analyze the swearing phrases in one of the holy scriptures, the holy Quran. This was done to determine whether swearing words exist in the sacred place or not. The researchers collected data by reading scripture and noting each indicated verse. The efforts were done three times to measure there was no any single datum which was left. Next, a data selection process was carried out to ensure the accuracy of the data by consulting Al Tabari's Tafseer book. After collecting a large amount of data, the researchers conducted a thorough analysis to determine: 1) the function of swearing words and 2) the origin of swearing phrases as depicted in holy text. The investigation revealed that there are two roles of cursing. According to the findings, the swear words acquired are employed to insult, to curse, and show furious emotions. The second discovery is that swearing words can come from five different sources. The categories are animal, mental, physical, safety, and respectability.Keywords: Swearing words, Holy Scripture, Qur’an.